Perception of municipal health managers regarding environmental health: Cerrado Araguaia Tocantins intermunicipal health consortium - de Morais, Vânia Soares; Chaves, André Preissler Loureiro (Saúde e Sociedade, 2016)
The initiatives of health consortiums (CIS), still little explored in Brazil, promote decentralization strategies toward overall goals of SUS for regionalization and the hierarchy of the offered services. These are innovations in the public sector to improve its management, provide specialized services and increase technological density for population, because the joint action between the municipalities may bring environmental and economic gains for these public services. The prospective study aimed to analyze the perception and actions of municipal managers that compose the intermunicipal Cerrado Araguaia Tocantins consortium, with regard to environmental health problems in the northern region of the state. Semi- structured interviews of 46 managers were analyzed through the discourse of the collective subject proposed by Lefèvre and Lefèvre, which revealed a broad view towards recognition of environmental health: the existence of local environmental problems that directly affect the population. However, there is no known interaction from the government on planning political and administrative actions of environmental health. The different parts involved in this subject, including those who work in the researched consortium, need to have a clear view of their participation in an active way, and that the organizational structures may support needed intersectoral strategies to meet the demands of today's health problems, including environmental problems.